Nyatnyono Village: A Nexus of Tarekat, Religious Culture and Tourism - Naim, Chanif Ainun (Universitas Islam Negeri Sunan Kalijaga, 2024)
This study explores the impact of tarekat (Sufi orders) on the religious culture of Nyatnyono Village, a rural community in Semarang Regency known for its rich Islamic traditions and emerging religious tourism. The village is home to several tarekat, including Qadiriyah wa Naqsyabandiyah (TQN), Naqsyabandiyah, Syattariyah, and Syadziliyah, all of which are intricately woven into the community's social and spiritual fabric. Insights gathered from interviews with local followers reveal that tarekat practices cultivate personal piety through spiritual guidance while fostering social solidarity and ethical behaviour. Under the mentorship of murshids (spiritual leaders), followers participate in dhikr, wirid, fasting, and communal gatherings, activities that facilitate spiritual development and strengthen communal relations. The findings indicate that tarekat practices play a vital role in shaping the cohesive religious culture of Nyatnyono Village, enhancing its resilience in times of crisis, such as during the COVID-19 pandemic. This research underscores the enduring significance of Sufism in Indonesia’s rural Muslim communities, particularly in its capacity to integrate religious tourism with spiritual and social unity.